2020
DOI: 10.1057/s41296-020-00414-4
|View full text |Cite
|
Sign up to set email alerts
|

Ethnocentric political theory, secularism and multiculturalism

Abstract: Your article is protected by copyright and all rights are held exclusively by Springer Nature Limited. This e-offprint is for personal use only and shall not be self-archived in electronic repositories. If you wish to self-archive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official publication or later and provided acknowledgement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In this section, we deconstruct this position, showing both that it presents a highly -and unnecessarily -reductive account of alienation and that its proponents have not successfully shown that their alternative is as objective as they claim. In order to keep this task manageable, we focus in particular on the versions of this argument found in recent work by Laborde and Laegaard (Laborde, 2017;Laborde and Laegaard, 2020;Laegaard, 2017Laegaard, , 2020.…”
Section: Deconstructing the Dichotomymentioning
confidence: 99%
“…In this section, we deconstruct this position, showing both that it presents a highly -and unnecessarily -reductive account of alienation and that its proponents have not successfully shown that their alternative is as objective as they claim. In order to keep this task manageable, we focus in particular on the versions of this argument found in recent work by Laborde and Laegaard (Laborde, 2017;Laborde and Laegaard, 2020;Laegaard, 2017Laegaard, , 2020.…”
Section: Deconstructing the Dichotomymentioning
confidence: 99%